Pre-mixed flow-state solidified soil slurry with self-sensing performance and preparation method of pre-mixed flow-state solidified soil slurry

Through the synergy between nano zinc oxide modified epoxy resin, conductive fibers and industrial waste residue, a premixed fluid-cured soil slurry was designed, which solved the problem of difficulty in realizing multiple functions in the prior art, achieved the combination of self-perception, high strength, fluidity and durability of the material, and showed excellent performance and self-repair ability in harsh environments.

CN119859040APending Publication Date: 2025-04-22CHINA CONSTRUCTION SIXTH ENGINEERING DIVISION CO LTD

Patent Information

Application Number
CN202510047645.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously realize multiple functions such as self-perception, high strength, high flowability, and high durability in one material, and the performance of the material is easily reduced in harsh environments.

Method used

Through the synergy between nano zinc oxide modified epoxy resin, conductive fibers and industrial waste residue, a premixed fluid-cured soil slurry was designed, which optimized the microstructure and interface combination of the material, and achieved the versatility and long-term stability of the material.

Benefits of technology

It achieves a perfect combination of self-perception, high strength, high fluidity and high durability. The material shows excellent corrosion resistance and stability in harsh environments, has self-healing potential, and has win-win results in environmental protection and economics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238966360000111
    Figure BDA0005238966360000111
  • Figure BDA0005238966360000121
    Figure BDA0005238966360000121
  • Figure BDA0005238966360000122
    Figure BDA0005238966360000122
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to premixed flow state solidified soil slurry with self-sensing performance and a preparation method of the premixed flow state solidified soil slurry. 200 to 220 parts of fine aggregate; 20-30 parts of industrial waste residue; 5-10 parts of an alkaline activator; 0.5 to 1.2 parts of modified epoxy resin; 70 to 90 parts of water; 1-3 parts of conductive fiber; 0.5-1 part of a water reducing agent; and 2-4 parts of an accelerator. Through the synergistic effect of the nano-zinc oxide modified epoxy resin, the conductive fibers and the industrial waste residues, perfect combination of self-sensing, high strength, high fluidity and high durability is achieved. Nano-zinc oxide is used as a seed crystal, so that ordered growth of C-S-H gel is promoted, interface bonding of epoxy resin and a cement matrix is improved, and a more compact and more stable microstructure is formed; in a long-term use process, the material shows certain self-repairing capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to a premixed fluidized solidified soil slurry with self-sensing performance and a preparation method thereof. Background Art

[0002] In recent years, with the continuous expansion and complexity of civil engineering projects, traditional premixed fluidized solidified slurry has been unable to meet the increasingly stringent engineering needs. Especially in special environments such as underground engineering and marine engineering, materials face multiple challenges, such as structural safety monitoring, impermeability, durability and other issues are becoming increasingly prominent.

[0003] The existing technologies mainly focus on the following aspects:

[0004] 1. Self-sensing materials: Currently, self-sensing concrete is mainly achieved by adding conductive materials such as carbon fiber and carbon nanotubes. However, these materials often have problems such as poor dispersion, high cost, and easy agglomeration, resulting in unstable sensing performance and insufficient long-term durability.

[0005] 2. High-performance concrete: The performance of concrete is improved by adding mineral admixtures, high-efficiency water reducers, etc. However, while improving the strength, the workability of the material is often reduced, increasing the difficulty of construction.

[0006] 3. Environmentally friendly concrete: Using industrial waste slag to replace part of the cement, although it reduces the cost and environmental load to a certain extent, it often leads to slow development of early strength and affects the progress of the project.

[0007] 4. Modified epoxy resin: used as a concrete modifier, it can improve the mechanical properties and durability of the material. However, traditional epoxy resin has poor compatibility with cement matrix, poor interface bonding, and long-term performance is difficult to guarantee.

[0008] The main problems of the existing technology:

[0009] 1. It is difficult to balance self-sensing ability and material performance: Increasing the content of conductive materials can enhance the sensing ability, but it often reduces the mechanical properties and workability of concrete.

[0010] 2. Conflict between early strength and long-term performance: Improving early strength usually requires increasing the amount of cement or using a quick-hardening agent, but this may lead to increased shrinkage and affect long-term durability.

[0011] 3. Multifunctionality is difficult to achieve: Existing technologies make it difficult to simultaneously achieve multiple functions such as self-sensing, high strength, high fluidity, and high durability in one material.

[0012] 4. Balance between environmental protection and performance: Although the use of industrial waste residues is environmentally friendly, it often leads to performance degradation, especially insufficient early strength.

[0013] 5. Insufficient control of microstructure: Existing technologies make it difficult to effectively control the evolution of the microstructure during cement hydration, resulting in unstable material properties.

[0014] 6. Long-term performance degradation: Especially in harsh environments, the self-sensing ability and mechanical properties of existing materials tend to degrade significantly over time.

[0015] In response to the above problems, there is an urgent need to develop a premixed fluidized solidifying slurry with self-sensing properties, which can simultaneously possess self-sensing ability, excellent mechanical properties, good workability and long-term durability, and can effectively utilize industrial waste residues during the production process to achieve environmental friendliness. Summary of the invention

[0016] The present invention aims to solve at least one of the problems of the prior art. Therefore, the present invention provides a premixed fluidized solidified soil slurry with self-sensing performance.

[0017] The premixed fluidized solidified soil slurry with self-sensing performance comprises the following components in parts by weight:

[0018] 100-150 parts of cementitious material;

[0019] 200-220 parts of fine aggregate;

[0020] 20-30 parts of industrial waste residue;

[0021] 5-10 parts of alkaline activator;

[0022] Modified epoxy resin 0.5-1.2 parts;

[0023] 70-90 parts of water;

[0024] 1-3 parts of conductive fiber;

[0025] Water reducing agent 0.5-1 part;

[0026] 2-4 parts of accelerating setting agent.

[0027] Preferably, the cementitious material is selected from one or more of ordinary Portland cement, sulphoaluminate cement and rapid hardening Portland cement.

[0028] Preferably, the fine aggregate is selected from one or more of river sand and machine-made sand; the industrial waste residue is selected from one or more of red mud and fly ash; and the alkaline activator is selected from one or more of calcium oxide and calcium hydroxide.

[0029] Preferably, the modified epoxy resin is prepared by the following steps:

[0030] (1) preparing zinc nitrate and hexamethylenetetramine into 0.05 mol / L aqueous solutions respectively, mixing equal volumes, hydrothermally reacting at 100° C. for 12 h, centrifuging and washing, and drying at 60° C. to obtain nano zinc oxide;

[0031] (2) dispersing the nano zinc oxide in a mixed solvent with an ethanol / water volume ratio of 1:9, adding (3-glycidyl propoxy) trimethoxy silane, reacting at 80° C. for 4 h, centrifuging and washing, and drying at 60° C. to obtain modified nano zinc oxide;

[0032] (3) The modified nano zinc oxide and bisphenol A epoxy resin were mixed in a mass ratio of 0.4:100, stirred at 60° C. for 2 h, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added in a mass ratio of 100:80:1.5, and cured at 90° C. for 4 h.

[0033] Preferably, the conductive fiber is selected from one or more of carbon fiber and steel fiber; the water reducer is selected from one or more of polycarboxylic acid-based high-performance water reducers and naphthalene-based water reducers; the accelerator is selected from one or more of sodium silicate and aluminum sulfate.

[0034] A method for preparing a premixed fluidized solidified soil slurry comprises the following steps: (1) pretreatment of conductive fibers; (2) dry material mixing; (3) wet mixing; (4) adding a modifier; (5) adding an admixture; and (6) vacuum stirring.

[0035] Preferably, the conductive fiber pretreatment step comprises: adding the conductive fiber to 20% of the total water volume, adding 0.1-0.2 parts by weight of sodium dodecylbenzene sulfonate as a dispersant, and ultrasonically dispersing at a frequency of 40 kHz for 30±2 minutes.

[0036] Preferably, the dry material mixing step comprises: putting the cementitious material, fine aggregate, industrial waste residue and alkaline activator into a dry powder mixer according to a proportion, and stirring at a speed of 120±10r / min for 5±0.5 minutes.

[0037] Preferably, the wet mixing step comprises: slowly adding the pretreated conductive fiber suspension and the remaining 80% of water to the dry material, and stirring at a speed of 180±10r / min for 10±1 minutes; the modifier adding step comprises: slowly adding the modified epoxy resin to the mixture, and stirring at a speed of 150±10r / min for 5±0.5 minutes.

[0038] Preferably, the step of adding an admixture comprises: first adding a water reducing agent, stirring for 2±0.2 minutes, and then adding an accelerating setting agent, stirring at a speed of 200±10r / min for 3±0.3 minutes; the vacuum stirring step comprises: transferring the mixture into a vacuum mixer, stirring at a speed of 100±10r / min for 5±0.5 minutes at a vacuum degree of -0.08 to -0.1MPa.

[0039] The beneficial effects of the present invention are:

[0040] 1. Multifunctional synergy: Through the synergistic effect of nano zinc oxide modified epoxy resin, conductive fiber and industrial waste residue, a perfect combination of self-sensing, high strength, high fluidity and high durability is achieved.

[0041] 2. Microstructure optimization: Nano zinc oxide as a seed promotes the orderly growth of CSH gel, while improving the interfacial bonding between epoxy resin and cement matrix, forming a denser and more stable microstructure.

[0042] 3. Self-repair potential: During long-term use, the material exhibits a certain self-repair ability, especially in terms of impermeability, which provides the possibility of extending the project life.

[0043] 4. Strong environmental adaptability: In harsh environments such as acid rain and freeze-thaw cycles, the material exhibits excellent corrosion resistance and stability.

[0044] 5. Balance between early strength and long-term performance: Through a carefully designed formula, it ensures high early strength without affecting the development of long-term performance.

[0045] 6. Environmental protection and economy: Effective utilization of industrial waste residues not only reduces costs, but also reduces environmental load, achieving a win-win situation in terms of performance and environmental protection.

[0046] 7. Intelligent monitoring: The electrical-mechanical coupling effect of materials provides a new means for structural health monitoring, which can achieve real-time monitoring throughout the entire life cycle.

[0047] In summary, the present invention overcomes many limitations of the prior art and provides a new type of premixed fluidized solidifying slurry with self-sensing ability, high performance, multi-function and environmental friendliness, which opens up a new direction for the development of civil engineering materials and has important theoretical significance and broad application prospects. DETAILED DESCRIPTION

[0048] The present invention will be further described below in conjunction with specific examples, but the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.

[0049] Example 1: A premixed fluidized solidified soil slurry with self-sensing performance

[0050] The premixed fluidized solidified soil slurry of this embodiment is composed of the following components (parts by weight):

[0051] 100 parts of ordinary Portland cement, 200 parts of river sand (SiO2 content 92%, fineness modulus 2.3), 20 parts of red mud (Al2O3 content 22%, Fe2O3 content 32%), 5 parts of calcium oxide (CaO content 95%), 0.5 parts of modified epoxy resin, 70 parts of water, carbon fiber (diameter 7μm, length 3mm, resistivity 1.5×10 -3 Ω·cm) 1 part, polycarboxylic acid high performance water reducing agent (solid content 28%, water reduction rate 27%) 0.5 parts, sodium silicate (modulus 2.4, Na2O content 26%) 2 parts.

[0052] The preparation method comprises the following steps:

[0053] (1) Conductive fiber pretreatment: 1 part of carbon fiber was added to 14 parts of water, and 0.1 part of sodium dodecylbenzene sulfonate was added, and ultrasonic dispersion was performed at a frequency of 40 kHz for 28 minutes.

[0054] (2) Dry material mixing: Put cement, river sand, red mud and calcium oxide into a dry powder mixer according to the proportion and stir at a speed of 110r / min for 4.5 minutes.

[0055] (3) Wet mixing: Slowly add the pretreated carbon fiber suspension and the remaining 56 parts of water to the dry material and stir at a speed of 170 r / min for 9 minutes.

[0056] (4) Adding modifier: slowly add the modified epoxy resin into the mixture and stir at a speed of 140 r / min for 4.5 minutes.

[0057] (5) Add admixtures: first add water reducer and stir for 1.8 minutes, then add sodium silicate and stir at 190 r / min for 2.7 minutes.

[0058] (6) Vacuum stirring: The mixture was transferred into a vacuum mixer and stirred at a speed of 90 r / min for 4.5 minutes under a vacuum degree of -0.08 MPa.

[0059] Wherein, the preparation method of modified epoxy resin is as follows:

[0060] (a) 0.05 mol / L zinc nitrate solution and 0.05 mol / L hexamethylenetetramine solution were mixed in equal volumes, subjected to hydrothermal reaction at 100°C for 12 h, centrifuged and washed, and dried at 60°C to obtain nano zinc oxide.

[0061] (b) dispersing nano zinc oxide in a mixed solvent of ethanol / water (volume ratio 1:9), adding (3-glycidylpropoxy)trimethoxysilane, reacting at 80° C. for 4 h, centrifuging and washing, and drying at 60° C. to obtain modified nano zinc oxide.

[0062] (c) The modified nano zinc oxide was mixed with bisphenol A epoxy resin in a mass ratio of 0.4:100, stirred at 60°C for 2 h, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added in a mass ratio of 100:80:1.5, and cured at 90°C for 4 h.

[0063] Example 2: A high-strength self-sensing premixed fluidized solidified soil slurry

[0064] The premixed fluidized solidified soil slurry of this embodiment is composed of the following components (parts by weight):

[0065] 125 parts of fast-hardening silicate cement, 210 parts of machine-made sand (SiO2 content 87%, fineness modulus 2.8), 25 parts of fly ash (SiO2+Al2O3+Fe2O3 content 75%, fineness 45μm sieve residue 30%), 7.5 parts of calcium hydroxide (Ca(OH)2 content 97%), 0.85 parts of modified epoxy resin, 80 parts of water, 2 parts of steel fiber (diameter 0.25mm, length 13.5mm, tensile strength 1100MPa), 0.75 parts of naphthalene-based water reducer (solid content 38%, water reduction rate 20%), and 3 parts of aluminum sulfate (Al2(SO4)3 content 18%).

[0066] The preparation method comprises the following steps:

[0067] (1) Conductive fiber pretreatment: 2 parts of steel fiber were added to 16 parts of water, 0.15 parts of sodium dodecylbenzene sulfonate were added, and ultrasonic dispersion was performed at a frequency of 40 kHz for 30 minutes.

[0068] (2) Dry material mixing: Put cement, machine-made sand, fly ash and calcium hydroxide into a dry powder mixer according to the proportion and stir at a speed of 120 r / min for 5 minutes.

[0069] (3) Wet mixing: Slowly add the pretreated steel fiber suspension and the remaining 64 parts of water to the dry material and stir at a speed of 180 r / min for 10 minutes.

[0070] (4) Adding modifier: Slowly add the modified epoxy resin into the mixture and stir at a speed of 150 r / min for 5 minutes.

[0071] (5) Add admixtures: first add water reducer and stir for 2 minutes, then add aluminum sulfate and stir at 200 r / min for 3 minutes.

[0072] (6) Vacuum stirring: The mixture was transferred into a vacuum mixer and stirred at a speed of 100 r / min for 5 minutes under a vacuum degree of -0.09 MPa.

[0073] The preparation method of the modified epoxy resin is the same as that of Example 1, but in step (c), the mass ratio of the modified nano zinc oxide to the bisphenol A epoxy resin is adjusted to 0.3:100.

[0074] Example 3: A fast-setting self-sensing premixed fluidized solidified soil slurry

[0075] The premixed fluidized solidified soil slurry of this embodiment is composed of the following components (parts by weight):

[0076] Sulphoaluminate cement 150 parts, river sand (SiO2 content 90%, fineness modulus 2.6) 220 parts, red mud (Al2O3 content 25%, Fe2O3 content 35%) 30 parts, calcium oxide (CaO content 92%) 10 parts, modified epoxy resin 1.2 parts, water 90 parts, carbon fiber (diameter 8.5μm, length 4mm, resistivity 1.6×10 -3 Ω·cm) 3 parts, polycarboxylic acid high performance water reducing agent (solid content 32%, water reduction rate 30%) 1 part, sodium silicate (modulus 2.7, Na2O content 28%) 4 parts.

[0077] The preparation method comprises the following steps:

[0078] (1) Conductive fiber pretreatment: 3 parts of carbon fiber were added to 18 parts of water, 0.2 parts of sodium dodecylbenzene sulfonate were added, and ultrasonic dispersion was performed at a frequency of 40 kHz for 32 minutes.

[0079] (2) Dry material mixing: Put cement, river sand, red mud and calcium oxide into a dry powder mixer according to the proportion and mix at a speed of 130r / min for 5.5 minutes.

[0080] (3) Wet mixing: Slowly add the pretreated carbon fiber suspension and the remaining 72 parts of water to the dry material and stir at a speed of 190 r / min for 11 minutes.

[0081] (4) Adding modifier: slowly add the modified epoxy resin into the mixture and stir at a speed of 160 r / min for 5.5 minutes.

[0082] (5) Add admixtures: first add water reducer and stir for 2.2 minutes, then add sodium silicate and stir at a speed of 210 r / min for 3.3 minutes.

[0083] (6) Vacuum stirring: The mixture was transferred into a vacuum mixer and stirred at a speed of 110 r / min for 5.5 minutes under a vacuum degree of -0.1 MPa.

[0084] The preparation method of modified epoxy resin is as follows:

[0085] (a) 0.05 mol / L zinc nitrate solution and 0.05 mol / L hexamethylenetetramine solution were mixed in equal volumes, subjected to hydrothermal reaction at 100° C. for 12 h, centrifuged and washed, and dried at 60° C. to obtain nano zinc oxide.

[0086] (b) dispersing nano zinc oxide in a mixed solvent of ethanol / water (volume ratio 1:9), adding (3-glycidylpropoxy)trimethoxysilane, reacting at 80° C. for 4 h, centrifuging and washing, and drying at 60° C. to obtain modified nano zinc oxide.

[0087] (c) The modified nano zinc oxide was mixed with bisphenol A epoxy resin in a mass ratio of 0.5:100, stirred at 60°C for 2 h, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added in a mass ratio of 100:80:1.5, and cured at 90°C for 4 h.

[0088] Example 4: A high-fluidity self-sensing premixed fluidized solidified soil slurry

[0089] The premixed fluidized solidified soil slurry of this embodiment is composed of the following components (parts by weight):

[0090] 137.5 parts of ordinary Portland cement, 215 parts of machine-made sand (SiO2 content 85%, fineness modulus 3.0), 27.5 parts of fly ash (SiO2+Al2O3+Fe2O3 content 70%, fineness 45μm sieve residue 34%), 8.75 parts of calcium hydroxide (Ca(OH)2 content 95%), 1.025 parts of modified epoxy resin, 85 parts of water, 2.5 parts of steel fiber (diameter 0.3mm, length 15mm, tensile strength 1000MPa), 0.875 parts of polycarboxylic acid-based high-performance water-reducing agent (solid content 30%, water reduction rate 25%), and 3.5 parts of aluminum sulfate (Al2(SO4)3 content 17%).

[0091] The preparation method comprises the following steps:

[0092] (1) Conductive fiber pretreatment: 2.5 parts of steel fiber were added to 17 parts of water, and 0.175 parts of sodium dodecylbenzene sulfonate were added, and ultrasonic dispersion was performed at a frequency of 40 kHz for 31 minutes.

[0093] (2) Dry material mixing: Put cement, machine-made sand, fly ash and calcium hydroxide into a dry powder mixer according to the proportion, and mix at a speed of 125 r / min for 5.25 minutes.

[0094] (3) Wet mixing: slowly add the pretreated steel fiber suspension and the remaining 68 parts of water to the dry material and stir at a speed of 185 r / min for 10.5 minutes.

[0095] (4) Adding modifier: slowly add the modified epoxy resin into the mixture and stir at a speed of 155 r / min for 5.25 minutes.

[0096] (5) Adding admixtures: first add water reducer and stir for 2.1 minutes, then add aluminum sulfate and stir at a speed of 205 r / min for 3.15 minutes.

[0097] (6) Vacuum stirring: The mixture was transferred into a vacuum mixer and stirred at a speed of 105 r / min for 5.25 min under a vacuum degree of -0.095 MPa.

[0098] The preparation method of modified epoxy resin is as follows:

[0099] (a) 0.05 mol / L zinc nitrate solution and 0.05 mol / L hexamethylenetetramine solution were mixed in equal volumes, subjected to hydrothermal reaction at 100°C for 12 h, centrifuged and washed, and dried at 60°C to obtain nano zinc oxide.

[0100] (b) dispersing nano zinc oxide in a mixed solvent of ethanol / water (volume ratio 1:9), adding (3-glycidylpropoxy)trimethoxysilane, reacting at 80° C. for 4 h, centrifuging and washing, and drying at 60° C. to obtain modified nano zinc oxide.

[0101] (c) The modified nano zinc oxide was mixed with bisphenol A epoxy resin in a mass ratio of 0.45:100, stirred at 60°C for 2 h, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added in a mass ratio of 100:80:1.5, and cured at 90°C for 4 h.

[0102] Comparative Example 1: Premixed fluidized solidified soil slurry without conductive fibers

[0103] This comparative example corresponds to Example 1, but the conductive fiber component is removed, in order to verify the contribution of the conductive fiber to the self-sensing performance.

[0104] Components (parts by weight): 100 parts of ordinary Portland cement, 200 parts of river sand, 20 parts of red mud, 5 parts of calcium oxide, 0.5 parts of modified epoxy resin, 71 parts of water, 0.5 parts of polycarboxylic acid-based high-performance water reducing agent, and 2 parts of sodium silicate.

[0105] The preparation method comprises the following steps:

[0106] (1) Dry material mixing: same as in Example 1.

[0107] (2) Wet mixing: add 71 parts of water to the dry material, and the rest is the same as in Example 1.

[0108] (3) Adding a modifier: Same as in Example 1.

[0109] (4) Adding admixture: Same as Example 1.

[0110] (5) Vacuum stirring: same as in Example 1.

[0111] The preparation method of the modified epoxy resin is the same as that of Example 1.

[0112] Comparative Example 2: High-strength premixed fluidized solidified slurry without modified epoxy resin

[0113] This comparative example corresponds to Example 2, but the modified epoxy resin is removed, the purpose of which is to verify the effect of the modified epoxy resin on the strength and durability of the material.

[0114] Components (parts by weight): 125 parts of rapid-hardening Portland cement, 210 parts of machine-made sand, 25 parts of fly ash, 7.5 parts of calcium hydroxide, 80.85 parts of water, 2 parts of steel fiber, 0.75 parts of naphthalene-based water reducer, and 3 parts of aluminum sulfate.

[0115] The preparation method comprises the following steps:

[0116] (1) Conductive fiber pretreatment: same as in Example 2.

[0117] (2) Dry material mixing: same as in Example 2.

[0118] (3) Wet mixing: slowly add the pretreated steel fiber suspension and the remaining 64.85 parts of water to the dry material, and the rest is the same as in Example 2.

[0119] (4) Adding admixture: Same as Example 2.

[0120] (5) Vacuum stirring: same as in Example 2.

[0121] Comparative Example 3: Rapidly setting premixed fluidized soil slurry using unmodified nano zinc oxide

[0122] This comparative example corresponds to Example 3, but uses nano zinc oxide without surface modification to replace the modified epoxy resin to verify the effect of surface modification on the dispersibility and material properties of nano zinc oxide.

[0123] Components (parts by weight): 150 parts of sulphoaluminate cement, 220 parts of river sand, 30 parts of red mud, 10 parts of calcium oxide, 0.6 parts of unmodified nano zinc oxide, 0.6 parts of epoxy resin, 90 parts of water, 3 parts of carbon fiber, 1 part of polycarboxylic acid-based high-performance water reducer, and 4 parts of sodium silicate.

[0124] The preparation method comprises the following steps:

[0125] (1) Conductive fiber pretreatment: same as in Example 3.

[0126] (2) Dry material mixing: Cement, river sand, red mud, calcium oxide and unmodified nano zinc oxide are put into a dry powder mixer according to the proportions, and the rest is the same as in Example 3.

[0127] (3) Wet mixing: same as in Example 3.

[0128] (4) Adding epoxy resin: Slowly add epoxy resin into the mixture and stir at a speed of 160 r / min for 5.5 minutes.

[0129] (5) Adding admixture: Same as Example 3.

[0130] (6) Vacuum stirring: same as in Example 3.

[0131] Preparation method of unmodified nano zinc oxide:

[0132] 0.05 mol / L zinc nitrate solution and 0.05 mol / L hexamethylenetetramine solution were mixed in equal volumes, subjected to hydrothermal reaction at 100°C for 12 hours, centrifuged and washed, and dried at 60°C to obtain nano zinc oxide.

[0133] Comparative Example 4: High-flowability premixed fluidized solidified soil slurry without industrial waste residue

[0134] This comparative example corresponds to Example 4, but the fly ash is removed, in order to verify the contribution of industrial waste residue to material performance and environmental protection.

[0135] Components (parts by weight): 165 parts of ordinary Portland cement, 215 parts of machine-made sand, 8.75 parts of calcium hydroxide, 1.025 parts of modified epoxy resin, 85 parts of water, 2.5 parts of steel fiber, 0.875 parts of polycarboxylic acid-based high-performance water reducing agent, and 3.5 parts of aluminum sulfate.

[0136] The preparation method comprises the following steps:

[0137] (1) Conductive fiber pretreatment: same as Example 4.

[0138] (2) Dry material mixing: Cement, machine-made sand and calcium hydroxide are put into a dry powder mixer according to the proportions, and the rest is the same as in Example 4.

[0139] (3) Wet mixing: same as Example 4.

[0140] (4) Adding a modifier: Same as Example 4.

[0141] (5) Adding admixture: Same as Example 4.

[0142] (6) Vacuum stirring: same as in Example 4.

[0143] The preparation method of the modified epoxy resin is the same as that of Example 4.

[0144] Comparative Example 5: Premixed fluidized solidified soil slurry without alkaline activator

[0145] This comparative example corresponds to Example 1, but calcium oxide is removed, in order to verify the effect of alkaline activators on the activation of industrial waste residues and the development of material strength.

[0146] Components (parts by weight): 100 parts of ordinary Portland cement, 200 parts of river sand, 20 parts of red mud, 0.5 parts of modified epoxy resin, 75 parts of water, 1 part of carbon fiber, 0.5 parts of polycarboxylic acid-based high-performance water reducing agent, and 2 parts of sodium silicate.

[0147] The preparation method comprises the following steps:

[0148] (1) Conductive fiber pretreatment: same as in Example 1.

[0149] (2) Dry material mixing: Cement, river sand and red mud are put into a dry powder mixer according to the proportions, and the rest is the same as in Example 1.

[0150] (3) Wet mixing: slowly add the pretreated carbon fiber suspension and the remaining 61 parts of water to the dry material, and the rest is the same as in Example 1.

[0151] (4) Adding a modifier: Same as in Example 1.

[0152] (5) Adding admixture: Same as Example 1.

[0153] (6) Vacuum stirring: same as in Example 1.

[0154] The preparation method of the modified epoxy resin is the same as that of Example 1.

[0155] Comparative Example 6: Premixed fluidized soil slurry using conventional epoxy resin

[0156] This comparative example corresponds to Example 2, but the modified epoxy resin is replaced by a conventional epoxy resin that has not been modified with nano-zinc oxide, so as to verify the effect of nano-zinc oxide modification on the performance improvement of the epoxy resin.

[0157] Components (parts by weight): 125 parts of fast-hardening Portland cement, 210 parts of machine-made sand, 25 parts of fly ash, 7.5 parts of calcium hydroxide, 0.85 parts of traditional epoxy resin, 80 parts of water, 2 parts of steel fiber, 0.75 parts of naphthalene-based water reducer, and 3 parts of aluminum sulfate.

[0158] The preparation method comprises the following steps:

[0159] (1) Conductive fiber pretreatment: same as in Example 2.

[0160] (2) Dry material mixing: same as in Example 2.

[0161] (3) Wet mixing: slowly add the pretreated steel fiber suspension and the remaining 64 parts of water to the dry material, and the rest is the same as in Example 2.

[0162] (4) Adding epoxy resin: Slowly add conventional epoxy resin into the mixture and stir at a speed of 150 r / min for 5 minutes.

[0163] (5) Adding admixture: Same as Example 2.

[0164] (6) Vacuum stirring: same as in Example 2.

[0165] Selection of traditional epoxy resin:

[0166] This comparative example uses a commercially available bisphenol A epoxy resin with an epoxy value of 0.48-0.54 eq / 100 g and a viscosity of 11000-14000 mPa·s (25° C.).

[0167] In order to comprehensively evaluate the performance of the premixed fluidized solidified slurry of the present invention, we designed the following experiments:

[0168] 1. Resistivity test: The four-probe method is used to measure the volume resistivity of the sample and evaluate the self-sensing ability of the material.

[0169] Experimental conditions: room temperature 25±2℃, relative humidity 50±5%

[0170] Steps: Prepare a sample of 40mm×40mm×160mm and test it after curing for 28 days.

[0171] 2. Compressive strength test: compressive strength test is carried out according to GB / T 50081-2019.

[0172] Experimental conditions: standard curing conditions (20±2℃, relative humidity above 95%)

[0173] Procedure: Prepare 100mm×100mm×100mm cubic specimens and conduct compressive strength tests at 3 days, 7 days and 28 days.

[0174] 3. Flowability test: refer to GB / T 2419-2005 for slump spread test.

[0175] Experimental conditions: room temperature 20±2℃

[0176] Procedure: Using a standard slump cone, measure the expanded diameter of the specimen.

[0177] 4. Anti-seepage performance test: Carry out anti-seepage performance test in accordance with GB / T 50082-2009.

[0178] Experimental conditions: water pressure 1.2MPa, lasting 72 hours

[0179] Steps: Prepare cylindrical specimens of Φ175mm×150mm and test them after curing for 28 days.

[0180] 5. Microstructure analysis: Scanning electron microscopy (SEM) was used to observe the microstructure of the samples.

[0181] Experimental conditions: Acceleration voltage 15kV, working distance 10mm

[0182] Steps: Take 28-day-old samples, spray gold and observe.

[0183] 6. Thermogravimetric analysis (TGA): evaluates the thermal stability and component composition of the material.

[0184] Experimental conditions: heating rate 10℃ / min, temperature range 25-800℃, nitrogen atmosphere

[0185] Procedure: Take 28-day-old sample powder for testing.

[0186] Table 1. Main performance indicators of the embodiments and comparative examples

[0187]

[0188]

[0189] Table 2. Compressive strength development of examples and comparative examples

[0190]

[0191] According to the test results, Example 2 performs best and can be regarded as the best embodiment of the present invention.

[0192] Result analysis and unexpected technical effects:

[0193] 1. Self-sensing ability: The resistivity of Examples 1-4 is in the range of 80-100 Ω·cm, while the resistivity of Comparative Example 1 (without conductive fiber) exceeds 10 6Ω·cm. This shows that the present invention successfully realizes the self-sensing function of the material. More interestingly, the resistivity of Example 3 is the lowest (82Ω·cm), which may be due to the synergistic effect of the carbon fiber and the fast-setting component to form a better conductive network structure.

[0194] 2. Mechanical properties: The 28-day compressive strength of Examples 1-4 all exceeded 42 MPa, which was significantly higher than that of each comparative example. In particular, Example 2 had a 28-day compressive strength of 48.3 MPa, which was 16.4% higher than that of Comparative Example 2 (without modified epoxy resin). This result demonstrates the key role of modified epoxy resin in enhancing the mechanical properties of materials. At the same time, we observed that the early strength development of the examples was also more rapid, which is of great significance to the shortening of the construction period.

[0195] 3. Fluidity: The fluidity of Examples 1-4 is within the range of 175-195 mm, meeting the construction requirements. It is worth noting that Example 4 has the highest fluidity (195 mm), which indicates that the present invention can achieve good workability while ensuring self-sensing ability and mechanical properties.

[0196] 4. Impermeability: Examples 2 and 4 achieved P10 impermeability grade, which is much better than the comparative example. This result was unexpected, indicating that nano zinc oxide modified epoxy resin not only improved the material strength, but also significantly improved its compactness and durability.

[0197] 5. Microstructure analysis: SEM observation results show that the hydration product in Example 2 is more compact, and the nano zinc oxide particles are evenly distributed in the cement matrix, forming a good interface transition zone, which explains its excellent mechanical properties and anti-permeability properties.

[0198] 6. Thermal stability: TGA results show that the mass loss of Example 2 in the range of 200-400°C is about 2.5% less than that of Comparative Example 6 (using traditional epoxy resin). This means that nano zinc oxide modified epoxy resin improves the thermal stability of the material, which is of great significance for improving the durability of the material in high temperature environments.

[0199] Unexpected technical effects and in-depth explanations:

[0200] 1. Synergistic reinforcement effect: In the present invention, a significant synergistic reinforcement effect is produced between the conductive fiber, the modified epoxy resin and the industrial waste residue. The 28-day compressive strength of Example 2 is 15-20% higher than the effect of simply adding these components. This may be due to the fact that the epoxy resin modified by nano zinc oxide plays a bridging role in the cement hydration process, enhancing the interface bonding between the conductive fiber and the cement matrix. At the same time, the active components of the industrial waste residue are fully excited in an alkaline environment, participate in the hydration reaction, and form a more compact microstructure.

[0201] 2. Self-repair potential: In the impermeability test, we unexpectedly found that under the action of water pressure for 72 hours, not only did Examples 2 and 4 not seep water, but a dense layer of calcium deposits formed on the surface of the sample. This shows that the material of the present invention has a certain self-repair ability. We speculate that this may be due to the secondary reaction of the nano zinc oxide modified epoxy resin at the microcracks, which promotes the deposition of calcium carbonate, thereby blocking the potential water seepage channel.

[0202] 3. Electromechanical coupling effect: When performing cyclic loading tests on Example 3, we found that the resistivity change of the material showed a good correspondence with the stress-strain curve. More interestingly, during the unloading process, the recovery rate of the resistivity was faster than the recovery rate of the strain. This electromechanical coupling effect not only enables the material to have the ability to monitor the stress state in real time, but also may provide a new means for evaluating the fatigue damage of the structure.

[0203] 4. Environmental adaptability: In the simulated acid rain (pH = 4.5) immersion test, Examples 1-4 showed excellent corrosion resistance, with a mass loss of no more than 0.5% in 28 days, while the mass loss of the comparative examples was generally between 1.5-2%. This result exceeded expectations, indicating that the material of the present invention has better durability in harsh environments. We believe that this may be due to the formation of a protective film on the surface of the material by the nano zinc oxide modified epoxy resin, which prevents the intrusion of acidic substances.

[0204] 5. Stability of the conductive network: Long-term durability tests show that after 300 freeze-thaw cycles, the resistivity of Examples 1-4 increased by no more than 10%, while the resistivity of Comparative Example 6 (using traditional epoxy resin) increased by nearly 30%. This shows that the conductive network in the present invention has excellent stability. We speculate that the nano zinc oxide modified epoxy resin plays a stress buffering role during the freeze-thaw process, reducing the generation of microcracks, thereby protecting the integrity of the conductive network.

[0205] 6. Structural optimization during curing: In-situ X-ray diffraction (XRD) studies have shown that the crystallinity of the CSH gel in Example 2 during the hydration process is significantly higher than that in the comparative example. This means that the microstructure of the material is more ordered, which is conducive to the improvement of mechanical properties. We believe that this may be due to the fact that nano zinc oxide plays the role of a seed during the hydration process, promoting the orderly growth of the CSH gel.

[0206] In summary, the present invention not only achieves the expected self-sensing function and mechanical performance improvement through the synergistic effect of multiple components, but also shows unexpected excellent effects in terms of impermeability, durability, environmental adaptability, etc. These findings provide new ideas and possibilities for the development of a new generation of intelligent, high-performance, and long-life civil engineering materials. At the same time, the multifunctional characteristics of the present invention are expected to simplify engineering design and construction processes, improve engineering quality and safety, and have broad application prospects.

[0207] Through the design of Example 6, we can better evaluate the effect of nano zinc oxide modification on the performance of epoxy resin. Combined with the previous test results, we can draw the following in-depth analysis:

[0208] 1. Mechanical properties: The 28-day compressive strength of Comparative Example 6 is 42.7 MPa, which is higher than Comparative Example 2 (41.5 MPa) without epoxy resin, but significantly lower than Example 2 (48.3 MPa). This indicates that nano zinc oxide modification significantly improves the reinforcing effect of epoxy resin on cement matrix.

[0209] 2. Microstructure: SEM observation shows that the interface bonding between the epoxy resin and the cement matrix in Comparative Example 6 is not as dense as that in Example 2. In Example 2, the nano zinc oxide particles act as anchor points to enhance the interface bonding between the epoxy resin and the cement matrix.

[0210] 3. Durability: After 300 freeze-thaw cycles, the resistivity of Comparative Example 6 increased by nearly 30%, while that of Example 2 increased by less than 10%. This indicates that the nano zinc oxide modification significantly improves the stability of the conductive network and the anti-freeze-thaw performance of the material.

[0211] 4. Impermeability: The impermeability grade of Comparative Example 6 is P8, which is lower than P10 of Example 2. This may be because the nano zinc oxide modified epoxy resin forms a denser network structure during the cement hydration process, effectively reducing the porosity of the material.

[0212] 5. Curing kinetics: Isothermal calorimetry studies have shown that the hydration heat release rate of the cement in Example 2 is about 15% faster than that in Comparative Example 6. This indicates that the nano zinc oxide modified epoxy resin may have a catalytic effect on the hydration process of the cement, promoting the development of early strength.

[0213] 6. Interface interaction: Fourier transform infrared spectroscopy (FT IR) analysis showed that new characteristic peaks appeared in Example 2, indicating that chemical bonding may have formed between the nano zinc oxide modified epoxy resin and the cement hydration product. This explains why Example 2 has better mechanical properties and durability.

[0214] 7. Thermal stability: Thermogravimetric analysis (TGA) results show that the mass loss of Example 2 in the range of 200-400°C is about 2.5% less than that of Comparative Example 6. This means that nano zinc oxide modification improves the thermal stability of epoxy resin, which is beneficial for the material to maintain performance in high temperature environments.

[0215] 8. Rheological properties: The fluidity of Comparative Example 6 (176 mm) is slightly lower than that of Example 2 (178 mm). This shows that the modification of nano zinc oxide not only does not reduce the workability of the material, but slightly improves it. We speculate that this may be because the nanoparticles reduce the entanglement between epoxy resin macromolecules and reduce the viscosity of the system.

[0216] Through the in-depth analysis of Example 6, we can more clearly see the key role of nano zinc oxide modified epoxy resin in the present invention. It not only improves the mechanical properties and durability of the material, but also improves the stability of the conductive network and the workability of the material. The realization of these comprehensive effects reflects the innovation and advancement of the present invention in material design, and provides important technical support for the development of a new generation of high-performance, multifunctional civil engineering materials.

[0217] The chemical mechanism of this material is as follows:

[0218] 1. Conductive fiber network: Carbon fiber or steel fiber forms a three-dimensional conductive network in the material, making the material conductive. When external stress causes microcracks, the conductive network is destroyed and the resistivity changes, thus achieving self-sensing function.

[0219] 2. Nano zinc oxide modified epoxy resin: Nano zinc oxide has a large specific surface area and can form a strong interface with epoxy resin. At the same time, nano zinc oxide can also catalyze the curing reaction of epoxy resin and increase the cross-linking density. This modified epoxy resin forms a composite structure with the cement matrix, significantly improving the mechanical properties and durability of the material.

[0220] 3. Activation of industrial waste residue: The active SiO2 and Al2O3 in red mud or fly ash are activated in an alkaline environment, participate in hydration reaction, generate CSH gel and CASH gel, and improve the later strength and density of the material.

[0221] 4. Rapid setting mechanism: Sodium silicate reacts quickly with Ca(OH)2 in cement to form CSH gel, which accelerates setting; aluminum sulfate reacts with C3A in cement to form calcium sulfate, which promotes rapid setting. By adjusting the amount of accelerator, the rate of these reactions can be controlled, thereby adjusting the initial setting time.

[0222] 5. Effect of water reducer: Polycarboxylic acid water reducer disperses cement particles through electrostatic repulsion and steric hindrance, reduces paste viscosity and improves fluidity. At the same time, it can also promote cement hydration and improve early strength.

[0223] 6. Alkaline activator: Calcium oxide or calcium hydroxide provides an alkaline environment, which on the one hand promotes the activation of industrial waste slag, and on the other hand accelerates the hydration reaction of cement and improves the early strength.

[0224] Advantages of this material in practical applications:

[0225] 1. Self-sensing function: By monitoring the resistance changes of the material, the stress state and crack development of the structure can be understood in real time, thus improving the safety of the project.

[0226] 2. Adjustability: The initial setting time is adjustable to adapt to different construction environments and requirements, such as grouting behind tunnel lining, underground continuous wall, etc.

[0227] 3. High performance: It has good fluidity, strength and impermeability, meeting the technical requirements of various underground projects.

[0228] 4. Environmental protection and economy: Utilize industrial waste to reduce costs and reduce environmental pollution.

[0229] 5. Multifunctionality: It integrates water stopping, self-detection and structural reinforcement to simplify the construction process.

[0230] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A premixed fluidized solidified soil slurry with self-sensing performance, characterized in that: The composition comprises the following components in parts by weight: 100-150 parts of cementitious material; 200-220 parts of fine aggregate; 20-30 parts of industrial waste residue; 5-10 parts of alkaline activator; Modified epoxy resin 0.5-1.2 parts; 70-90 parts of water; 1-3 parts of conductive fiber; Water reducing agent 0.5-1 part; 2-4 parts of accelerating setting agent.

2. The premixed fluidized solidified soil slurry according to claim 1, characterized in that: The cementitious material is selected from one or more of ordinary silicate cement, sulphoaluminate cement and rapid hardening silicate cement.

3. The premixed fluidized solidified soil slurry according to claim 1, characterized in that: The fine aggregate is selected from one or more of river sand and machine-made sand; the industrial waste residue is selected from one or more of red mud and fly ash; and the alkaline activator is selected from one or more of calcium oxide and calcium hydroxide.

4. The premixed fluidized solidified soil slurry according to claim 1, characterized in that: The modified epoxy resin is prepared by the following steps: (1) preparing zinc nitrate and hexamethylenetetramine into 0.05 mol / L aqueous solutions respectively, mixing equal volumes, hydrothermally reacting at 100° C. for 12 h, centrifuging and washing, and drying at 60° C. to obtain nano zinc oxide; (2) dispersing the nano zinc oxide in a mixed solvent with an ethanol / water volume ratio of 1:9, adding (3-glycidyl propoxy) trimethoxy silane, reacting at 80° C. for 4 h, centrifuging and washing, and drying at 60° C. to obtain modified nano zinc oxide; (3) The modified nano zinc oxide and bisphenol A epoxy resin were mixed in a mass ratio of 0.4:100, stirred at 60° C. for 2 h, methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol were added in a mass ratio of 100:80:1.5, and cured at 90° C. for 4 h.

5. The premixed fluidized solidified soil slurry according to claim 1, characterized in that: The conductive fiber is selected from one or more of carbon fiber and steel fiber; the water reducer is selected from one or more of polycarboxylic acid high-performance water reducer and naphthalene water reducer; the quick-setting agent is selected from one or more of sodium silicate and aluminum sulfate.

6. A method for preparing the premixed fluidized solidified slurry according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Conductive fiber pretreatment; (2) Dry material mixing; (3) Wet mixing; (4) Adding modifiers; (5) Adding admixtures; (6) Vacuum mixing.

7. The preparation method according to claim 6, characterized in that: The conductive fiber pretreatment step comprises: adding the conductive fiber to 20% of the total water volume, adding 0.1-0.2 parts by weight of sodium dodecylbenzene sulfonate as a dispersant, and ultrasonically dispersing at a frequency of 40kHz for 30±2 minutes.

8. The preparation method according to claim 6, characterized in that: The dry material mixing step comprises: putting the cementitious material, fine aggregate, industrial waste residue and alkaline activator into a dry powder mixer according to a proportion, and stirring at a speed of 120±10r / min for 5±0.5 minutes.

9. The preparation method according to claim 6, characterized in that: The wet mixing step comprises: slowly adding the pretreated conductive fiber suspension and the remaining 80% of water into the dry material, and stirring at a speed of 180±10r / min for 10±1 minutes; the modifier adding step comprises: slowly adding the modified epoxy resin into the mixture, and stirring at a speed of 150±10r / min for 5±0.5 minutes.

10. The preparation method according to claim 6, characterized in that: The step of adding admixtures comprises: first adding a water reducing agent, stirring for 2±0.2 minutes, then adding an accelerating setting agent, and stirring at a speed of 200±10r / min for 3±0.3 minutes; the step of vacuum stirring comprises: transferring the mixture into a vacuum mixer, and stirring at a speed of 100±10r / min for 5±0.5 minutes at a vacuum degree of -0.08 to -0.1MPa.

Citation Information

Patent Citations

  • Self-induction conductive cement composite material and preparation method thereof

    CN115385621A

  • Composite pile premixed flow-state solidified soil slurry and preparation method thereof

    CN116655339A

  • Self-sensing and self-compacting solidified soil for roadbed monitoring and preparation method and application of self-sensing and self-compacting solidified soil

    CN118084418A

Cited By

  • Premixed high-strength flow-state solidified soil and preparation method thereof

    CN120328979A

  • Premixed high-strength fluidized solidified soil and preparation method thereof

    CN120328979B

  • Nano-composite hybrid activator for high-glass-phase building materials and preparation method of nano-composite hybrid activator

    CN120504512A

  • Crack-control self-repairing type intelligent ultrahigh-durability concrete as well as preparation method and application thereof

    CN121021063A